Hippocampal insulin signaling and neuroprotection mediated by physical exercise in Alzheimer´s Disease - Kuga, Gabriel Keine (2017)
Abstract Epidemiological studies indicate continuous increases in the prevalence of Alzheimer’s Disease (AD) in the next few decades. The key feature of this disease is hippocampal neurodegeneration. This structure has an important role in learning and memory. Intense research efforts have sought to elucidate neuroprotective mechanisms responsible for hippocampal integrity. Insulin signaling seems to be a very promising pathway for the prevention and treatment of AD. This hormone has been described as a powerful activator of neuronal survival. Recent research showed that reduced insulin sensitivity leads to low-grade inflammation, and both phenomena are closely related to AD genesis. Concomitantly, exercise has been shown to exert anti-inflammatory effects and to promote improvement in insulin signaling in the hippocampus, which supports neuronal survival and constitutes an interesting non-pharmacological alternative for the prevention and treatment of AD. This review examines recent advances in understanding the molecular mechanisms involved in hippocampal neuroprotection mediated by exercise.